A holstein heifer infected with Neospora caninum NcUru3 congenitally transmits this strain to a viable offspring although infection does not protect her from aborting by a different N. caninum genotype in the subsequent gestation - Giannitti, Federico; Aráoz, Virginia; da Silva Silveira, Caroline; Francia, María E.; Robello, Carlos; Cabrera, Andrés (Frontiers in Veterinary Science, 2022)
Neospora caninum is a leading cause of bovine abortion worldwide. Although the genetic diversity of this apicomplexan parasite has long been recognized, there is little information on whether infection by a given genotype impairs protective immunity against abortion induced by different genotypes. Here, we provide evidence supporting that natural subclinical infection with isolate NcUru3 of N. caninum in a pregnant heifer did not provide protection against abortion caused by a different N. caninum genotype in the subsequent gestation. A Holstein heifer delivered a healthy calf congenitally infected with N. caninum. Specific anti-N. caninum IgG was detected by indirect ELISA in sera obtained from the dam at calving and the calf before ingestion of colostrum, indicating in utero exposure. Neospora caninum strain NcUru3 was isolated and characterized by multilocus microsatellite typing from the brain of this neonate euthanized at 9 days of age. Sixty days after calving, the cow got pregnant, although she aborted spontaneously at ~6 months of gestation. Pathologic examination of the aborted fetus and placenta revealed typical lesions of neosporosis, including encephalitis, myocarditis, hepatitis, myositis, and placentitis. Neospora caninum DNA was amplified from the fetal brain, heart, kidney, and placenta, and multilocus microsatellite typing revealed a genotype that differed from isolate NcUru3 at the MS6A level. Serum obtained from the dam at the time of abortion had IgG that cross-recognized isolate NcUru3, as demonstrated by immunoblotting, indicating that the humoral immune response did not prevent the other genotype from infecting the fetus and inducing fetoplacental lesions and abortion.